1979
DOI: 10.1017/s0014479700000569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preceding Grain Legumes on Dryland Pearl Millet in NW India

Abstract: SUMMARYYields of pearl millet were significantly increased when grown after legume crops such as groundnut (22·6%), cowpea (24·2%) or pigeonpea (12·1%) instead of after pearl millet. A previous crop of short-duration mung did not affect the yield of pearl millet. Benefits from previous crops of groundnut and cowpea were equivalent to about 60 kg N/ha applied to a pearl millet crop following a previous crop of pearl millet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…Many tropical grain legumes have the capacity to increase soil productivity thereby benefiting the subsequent crop though wide variations may occur in their capacity to do so. Whereas Jones (1974) found greater benefit from groundnuts than from cow pea on a subsequent crop of maize, Giri & De (1979) reported that the yield of pearl millet was in-creased by 24-2% after cow pea, 22-6% after groundnuts and 12-1 % after pigeon pea. Quantitatively these benefits from cow pea and groundnuts were equivalent to 60 kg N/ha applied to pearl millet after a cereal, while that from pigeon pea was of the order of 30 kg N/ha.…”
Section: Discussionmentioning
confidence: 96%
“…Many tropical grain legumes have the capacity to increase soil productivity thereby benefiting the subsequent crop though wide variations may occur in their capacity to do so. Whereas Jones (1974) found greater benefit from groundnuts than from cow pea on a subsequent crop of maize, Giri & De (1979) reported that the yield of pearl millet was in-creased by 24-2% after cow pea, 22-6% after groundnuts and 12-1 % after pigeon pea. Quantitatively these benefits from cow pea and groundnuts were equivalent to 60 kg N/ha applied to pearl millet after a cereal, while that from pigeon pea was of the order of 30 kg N/ha.…”
Section: Discussionmentioning
confidence: 96%
“…cow pea as 40-60 kg N/ha (Giri & De 1979;Narwal el al. 1981) and that of fallow as 37-100 kg N/ha (Rao, Dart & Sastry, 1983;Doughton & Mackenzie, 1984).…”
Section: -065mentioning
confidence: 99%
“…Sole cropping of groundnuts has shown considerable residual effects on subsequent cereal crops (Jones, 1974;Giri and De, 1979;Nambiar and Dart, 1980). A reduction in the N 2 -fixation of intercropped groundnuts suggests that the residual effect in these situations may be less than that expected from the general growth and yield of the legume crop.…”
Section: Fig 2 Nodulation (A) and Nj-fixation (B) Of Sole Crop Groumentioning
confidence: 99%